Analisis Pendekatan Moral dalam Naskah Drama RT 0 RW 0 Karya Iwan Simantupang - Dwi Noviyanti; Nadia Widodo; Joko Purwanto (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This research aims to reveal the moral values contained in the play RT 0 RW 0 by Iwan Simatupang using a moral approach. This drama describes the social life of marginalized communities who are full of limitations but still show an unyielding spirit. The method used is descriptive with data analysis techniques in the form of observation of the script text and identification of dialog quotes that contain moral values. The results showed that moral values in the script are divided into three aspects, namely individual moral values, social moral values, and religious moral values. Eight quotations with moral values were found: three individual values, four social values, and two religious values. Social moral value is the most dominant aspect, reflecting the importance of solidarity, compassion, and care among others in the social life of the lower-class community. This research shows that literary works, especially drama, can be an effective means of conveying moral messages to readers and audiences.